Identification of vulnerable areas in Bago City using the drastic approach and simulation of lead transport in the underlying aquifer using ASMWIN - Pandan, Mary Ann Torres (2000)
The DRASTIC system which is an assessment method based on the hydrogeological setting was used to determine the relative vulnerability to groundwater contamination in Baguio City. Seven parameters, namely (1) D - depth to groundwater (2) R - recharge rate (3) A - aquifer media (4) S - soil media (5) T - topography (slope) (6) I - impact of the vadose zone and (7) C - conductivity (hydraulic) of the aquifer were used to assess the potential for contamination in the study area. Highly vulnerable areas were identified in the coastal areas while the least vulnerable areas were in the mountainous regions. Using the DRASTIC index, possible sources of contamination were evaluated. The one which presents the greatest risk was established and this is the open dumpsite. For this type of source, the threat of leachate infiltration was considered and its annual volume was calculated at 27320 cu.m. The heavy metals in the leachate were of major concern specifically, lead (Pb) and based on monitoring data from a similar disposal site, its concentration was assumed to be 0.397 mg/L.
Modeling of the transport of the lead component in the leachate was done using the Aquifer Simulation Model for Windows (ASMWIN). Hydrologic models of the two aquifer systems within the study area were done and the results were used to model the movement of the lead and its contaminant plume. Results indicate that in the confined aquifer, the influence of lead will have a minimal environmental impact on the area. In the unconfined aquifer, it was determined that the contamination will not have any significant effect.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman.
Keywords: Groundwater -- Pollution -- Philippines -- Bago City; Groundwater flow -- Philippines -- Bago City; Aquifers -- Philippines -- Bago City